EFEKTIVITAS ANALISIS AKAR MASALAH “METODE PEMBELAJARAN” PADA RAPOR PENDIDIKAN SEKOLAH DASAR PENGGERAK ANGKATAN I - Jannah, Ukhti Raudhatul; Basori, Indrianto Setyo; Amiruddin, Mohammad; Rifanda, Akhmad Riski; Dwi Agustin, Sisca Patricia (Kwangsan: Jurnal Teknologi Pendidikan, 2023)
The objectives of this research are (a) to analyze the effectiveness of the root of the problem related to learning methods in the education report card at the First Generation Pengpeng Elementary School, (b) to analyze the impact of this problem on the learning process and achievement of student learning outcomes, (c) to prepare recommendations and improvement strategies to address identified problems. The research method that will be used in this research is qualitative research which involves various approaches, such as classroom observations, interviews with teachers and students, as well as document studies (document analysis) related to the learning methods applied. The research subjects were 90 students with 18 students in grades 1-6 in each school, 5 principals, and 2 elementary school teachers for Class I (SDN Pandian I, SDN Patian II, SDN Bataal Barat I, SDN Banbaru I, SDN Sapeken IV). The results of this research are (a) the results of priority recommendations in education report cards carried out by schools (Education units) are very effective in overcoming the root of the problem of "learning methods". (b) the impact of teachers having changed conventional learning methods into innovative and meaningful learning in accordance with the priority improvement program recommended in the Education Report Cards. (c) recommendations and improvement strategies to overcome problems identified through innovative and meaningful learning methods such as group discussions, games, learning with teaching aids or learning media. The results of this research can be used as recommendations for other schools in improving their education report cards with the same root problem, namely "learning methods".AbstrakTujuan dari penelitian ini adalah (a) menganalisis keefektifan akar masalah yang terkait dengan metode pembelajaran pada rapor pendidikan di Sekolah Dasar Penggerak Angkatan I, (b) menganalisis dampak dari masalah tersebut terhadap proses pembelajaran dan pencapaian hasil belajar siswa, (c) menyusun rekomendasi dan strategi perbaikan untuk mengatasi masalah yang diidentifikasi. Metode penelitian yang akan digunakan dalam penelitian ini penelitian kualitatif yang melibatkan berbagai pendekatan, seperti observasi kelas, wawancara dengan guru dan siswa, serta studi dokumen (analisis dokumen) terkait metode pembelajaran yang diterapkan. Subjek penelitiannya adalah 90 siswa dengan masing-masing sekolah 18 siswa kelas 1-6, 5 kepala sekolah, dan 2 masing-masing guru sekolah dasar penggerak Angkatan I (SDN Pandian I, SDN Patian II, SDN Bataal Barat I, SDN Banbaru I, SDN Sapeken IV). Hasil penelitian ini adalah (a) hasil prioritas rekomendasi di rapor pendidikan yang dilakukan sekolah (satuan Pendidikan) sangat efektif dalam mengatasi akar masalah dari “metode pembelajaran”. (b) dampaknya guru-guru telah mengubah metode pembelajaran konvensional menjadi pembelajaran inovatif dan bermakna sesuai pada program benahi di prioritas rekomendasi pada rapor Pendidikan. (c) rekomendasi dan strategi perbaikan untuk mengatasi masalah yang diidentifikasi melalui metode pembelajaran inovatif dan bermakna seperti diskusi kelompok, permainan, pembelajaran dengan alat peraga atau media pembelajaran. Hasil penelitian ini dapat dijadikan rekomendasi bagi sekolah lain dalam memperbaiki rapor Pendidikannya dengan akar masalah yang sama yaitu “metode pembelajaran”.